The Impact of Social Media Marketing on Algerian Tourists' Attitudes Towards Domestic Tourism: The Facebook Platform as a Model - Bensehih, Abdelkader; Medjahdi, Fateh; Brahimi, Cheraf (Journal of Ecohumanism, 2026)
This study examines and analyzes the impact of Facebook marketing on Algerian tourists' attitudes toward domestic tourism. It combines theoretical grounding with a quantitative field test. The study uses a conceptual model in which Facebook marketing is treated as a multidimensional independent variable. Its dimensions are the quality and diversity of marketing content, interactivity, the credibility and quality of influencer content, relevance and trendiness, and customization. Tourists' attitudes are treated as the dependent variable. They are measured through three dimensions: the cognitive, affective, and behavioral dimensions. The study adopts the descriptive analytical method. Data were collected through an online questionnaire addressed to a sample of Algerian tourists. The final sample included 244 valid responses, which were analyzed using SPSS 24. The results show a strong and statistically significant effect of Facebook marketing on Algerian tourists' attitudes toward domestic tourism. They also show that customization is the strongest determinant of Algerian tourists' attitudes. It is followed by relevance and trendiness, then interactivity, and then the credibility and quality of influencer content. By contrast, the quality and diversity of marketing content did not maintain an independent effect in the multiple regression model.